Sovereign Asset and Liability Management in Emerging Market Countries : The Case of Uruguay - Amante, Andre (IMF Working Papers; Working Paper ;, 2019)
This paper provides an overview of the strategic and operational issues as well as institutional challenges, related to the implementation of the Sovereign Asset and Liability Management (SALM) approach. Application of an SALM framework allows the authorities to identify and monitor sovereign exposure mismatches; increase resilience to foreign currency and interest rate risks; and thus, strengthen financial stability; and implement more cost-effective management of the public-sector debt. The analysis is based on emerging market (EM) countries and illustrated by the experience of Uruguay, using data as of end-2017.